2022
DOI: 10.6023/cjoc202106051
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Photoelectric Co-catalysis

Abstract: Photochemical and electrochemical reactions, which are mild and green, have been widely used in organic synthesis in recent years. To push the limits of both synthetic technologies, organic chemists have focused on using these two strategies to promote organic transformation in a single reaction system. A series of photoelectrochemical strategies have been developed, and the main one at present is electrochemically mediated photoredox catalysis. In addition, photoexcitation-assisted electroredox strategies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…As shown in Table 2 (entry 19), the ortho-substituted bromobenzenes (1-bromo-2chlorobenzene) exhibited moderate reactivity with a product yield of 82%, which could originate from the steric hindrance during the cross-coupling reaction. As expected, a high yield of the coupling products was observed with para-substituted aryl halides (Table 2, entries [16][17][18]. In contrast, meta-substituted aryl halides exhibited lower activity than that of para-and ortho-substituents, which likely resulted from the steric hindrance and electronic effects (Table 2, entry 20).…”
Section: Catalysis Science and Technology Papersupporting
confidence: 69%
See 1 more Smart Citation
“…As shown in Table 2 (entry 19), the ortho-substituted bromobenzenes (1-bromo-2chlorobenzene) exhibited moderate reactivity with a product yield of 82%, which could originate from the steric hindrance during the cross-coupling reaction. As expected, a high yield of the coupling products was observed with para-substituted aryl halides (Table 2, entries [16][17][18]. In contrast, meta-substituted aryl halides exhibited lower activity than that of para-and ortho-substituents, which likely resulted from the steric hindrance and electronic effects (Table 2, entry 20).…”
Section: Catalysis Science and Technology Papersupporting
confidence: 69%
“…Combining the benefits of photocatalysis and electrocatalysis (e.g., mild reaction conditions, high efficiency, low-cost equipment and environmental compatibility), photoelectrocatalysis is particularly intriguing in the field of green organic transformations, such as redox reactions, coupling reactions and beyond. [13][14][15][16] For photoelectrocatalytic organic synthesis, the exploration of suitable photoelectrode materials, which usually have a significant impact on both the reaction thermodynamics and electron transfer kinetics, is pivotal for achieving the highly selective transformation of organic compounds. 17,18 Interestingly, it has been reported that ordered TiO 2 nanotube arrays (NTAs) exhibit excellent photoelectric properties due to their high light absorption coefficient, oriented charge transfer route and good stability.…”
Section: Introductionmentioning
confidence: 99%